Analysis of the Meaning of Pragmatics of Fatisanity in Class Discussions - Estuning Dewi Hapsari; Dedi Richi Rizaldy; Isyaau Akhsanil Khakim (English Department FBS UNP, 2021)
This research aims to obtain the meaning and the appearance of phatic in a class discussion. This research used the descriptive qualitative method. The data collection methods were in the forms of listening and speaking. The data collection techniques used writing and recording. The obtained data were analyzed using the padan method. The data analysis consisted of data reduction, data display, and verification. Based on the results of the research, there were four appearances and the meanings of phatic pragmatics in the discussion. The meanings of phatic pragmatics consisted of a) the phatic pragmatic meant an acceptance, b) the phatic pragmatic meant the inviting, c) the pragmatic meant a refusal d) the pragmatic meant gratitude. There were four purposes of phatic pragmatics, namely, 1) to respect others, 2) to take care of other people’s feelings, 3) to enhance cooperation, and 4) to improve humor.